The Corporate Rescue for Companies during the COVID-19 Pandemic in Indonesia: Prospects for the Concept of Deeds of Arrangement and Administration Order - Amboro, F. Yudhi Priyo (Technium Social Sciences Journal, 2021)
The COVID-19 pandemic has an impact to all countries, including Indonesia. This raises the problem of debt default. Rather than bankruptcy and suspension of payment (PKPU), it is better to look an alternative that become a savior for the company. This research explores the concept of Deeds of Arrangement and Administration Order according to United Kingdom law, and looking at the prospects for the concept of Deeds of Arrangement and Administration Order for Indonesia. It is a normative juridical research, and it was processed with a qualitative approach supported by a comparative legal analysis. The conclusions of this research show that the concepts of the Deeds of Arrangement and Administration Order are similar to the bankruptcy and PKPU schemes also have differences. The differences on the Deeds of Arrangement are how to register, the agreement is passed on a non-litigation basis and determined by the court, and no publication is required. The differences on the Administration Order is the mandatory debtor’s company management taking-over, the applicants, the administrators which can be appointed outside the court without court approval, and the administrator will make a corporate rescue proposal. The concept of the Deeds of Arrangement which is a contractual non-litigation and the Administration Order which provides a better corporate management role, is the right solution during the COVID-19 pandemic rather than bankruptcy and PKPU, as well as other litigation. The temporary character of the COVID-19 pandemic condition is the basis of this thought, so a solution concept that leads to maximization of the corporate rescue rather than liquidation, is needed.